The effects of porcine somatotropin (pST) dosage and dietary lysine level on growth performance and carcass characteristics of finishing swine - Schricker, B.R.; Stoner, G.R.; Danler, R.J.; Thaler, R.C.; Kenny, B.P.; Hurt, S.S.; Fitzner, G.E.; Apple, J.; Warren, K.; Goodband, Robert D.; Nelssen, Jim L.; Hines, Robert H.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and forty-four finishing pigs (initial weight 126 lb) were utilized to determine the effects of PST dosage (4 or 8 mg PST' head^-1day^-1 ) and dietary lysine level (.8, 1,0, 1.2, or 1.4%) on growth performance and carcass characteristics. Pigs were injected daily in the extensor muscle of the neck with either 4 or 8 mg PST and fed a pelleted corn-soybean meal-sesame meal diet containing .8% lysine. Additional lysine levels of 1.0, 1.2, and 1.4% were provided by L-lysine HCl. Control pigs (placebo injection) received the .8% lysine diet. All diets were formulated to contain at least 220% of NRC (1979) recommendations for other amino acids, vitamins and minerals. There were no PST x lysine interactions for any observed traits (P>,1 0), so only main effects are reported. Increasing level of dietary lysine resulted in linear improvements in average daily gain (ADG) and feed conversion (F/G) in PST treated pigs. Adjusted backfat thickness (ABF) was lowered (linear P<.05), whereas longissimus muscle area (LMA) was increased (linear P<.05) with increasing lysine level. Pigs injected with 8 mg PST had similar ADG compared to 4 mg PST-treated pigs, and both were greater than controls (linear and quadratic P < .05%). Increasing PST dosage improved F/G (linear and quadratic P < .05), LMA and reduced ABF (linear P < .05). Urea concentrations determined in plasma on day 28 decreased (linear and Quadratic P<.05) with increasing lysine level, whereas free fatty acids and insulin tended to increase (P<.10). Porcine somatotropin dosage decreased urea concentrations while glucose, insulin and free fatty acid concentrations increased (linear and quadratic P < .05) in plasma. Trimmed ham and loin weights were increased slightly (P >.10) by increasing dietary lysine level and were also increased (linear P < .10) by PST dosage.
Keywords: Swine; Porcine somatotropin; Dosage; Lysine requirement; Growth performance; Carcass traits; Finishing pigs